Linkage Network Structures of Farmers: Analysing FPOs of M.P. and Bihar in India - Singh, Ashish; Singh, Rashmi; Nain, Manjeet Singh; Mishra, J R; Kumar, Pramod; Sharma, D K; Paul, Ranjit Kumar (Indian Journal of Extension Education, 2023)
Effective linkages among farmers play a crucial role in fostering growth within the agriculture sector. This study conducted during 2020-23 utilizes social network analysis to examine the backward and forward agribusiness linkages of farmers in Dairy Farmer Producer Organizations (FPOs) in Madhya Pradesh and Bihar. Through focused group discussions, a comprehensive list of private and government institutions acting as linkage actors for each FPO were compiled. The findings highlight that farmers primarily rely on strong informal ties for accessing agricultural information and services. Furthermore, a disparity is observed between the FPOs in Bihar and Madhya Pradesh, with the former having a smaller number of linkage actors. The FPO in Bihar demonstrates stronger associations with government institutions and officials, while the FPO in Madhya Pradesh exhibits stronger connections with private entities, including the food processing industry, artificial insemination (AI) technicians, and veterinary doctors. The study provides valuable insights into the connectedness of network actors, underscores the importance of multi-actor alliances, and emphasizes the implications of centrality measures in determining network dynamics.
Keywords: Agribusiness linkages; Network analysis; Linkage networks; Farmer Producer Organisation (FPO)